IDENTIFIKASI PENGETAHUAN KESIAPSIAGAAN MASYARAKAT KELOMPOK RENTAN LANSIA DALAM MENGHADAPI BENCANA ERUPSI GUNUNG SEMERU DI DUSUN WONORENGGO DESA SUMBERMUJUR KABUPATEN LUMAJANG - Wibowo, Nugroho Ari (Indonesian Academia Health Sciences Journal, 2023)
Objective: The purpose of this study was to determine the community's preparedness for the elderly vulnerable group against the eruption of Mount Semeru in Wonorenggo village Methods: The research design used is descriptive with the population being all elderly vulnerable groups in Wonorenggo with 64 respondents taken Results and Conclusion: It is shown that 68.8% lack of knowledge about disasters, 68.8% lack of knowledge of preparation when disasters take place and 68.8% lack of knowledge about early warning systems. The conclusion of this study is that there is still a lack of disaster readiness for volcanic eruptions